Experimental verification and simulation of two stages positive output cascade boost converter super-lift DC/DC Luo-converter - Hammoda, Ahmed; Buamud, Mohammed S.; Tamasas, Mohamed Elrais; Mohamed, Adel; Khalil, Ashraf F.; Nasr, Mahmoud Shaker; Khan, Sheroz (Institute of Electrical and Electronics Engineers Inc., 2018)
DC/DC converters have been developed very quickly. Since 1920s there have been more than 500 DC/DC converters topologies developed. Advanced DC/DC converter have been developed and created by Luo and. Ye in 2001. The aim of this study is to investigate and state a designed method to evaluate the advanced DC/DC converter. The design should guarantee working in a continuous conduction mode and to improved system performance. Many researches and studies have been made for the converter. The two stages positive output cascade boost converter super-lift DC/DC Luo-converter is chosen as the case study of this paper. The system has been implemented over a wide range of experimental work and has been implemented in MATLAB/SIMULINK. Simulations and experimental results have been compared towards each other.